A study of language-related episodes in online English-medium instruction classes in high schools in South Korea. (July 2022) - Hong, Jiye
Abstract: In both face-to-face and online settings, attention to language during interpersonal interaction is essential for students' academic English development in English-medium instruction (EMI) classes. This article reports on a study of attention to language spontaneously arising in two different online EMI classes (world history and mathematics) in high schools in Korea. The frequency and nature of language-related episodes (LREs), any instances where teachers and students talk about the language they use, identified in the transcripts of class recording and synchronous text-based chat were analysed. Transcribed interview recordings were also analysed to explore the challenges for the EMI teachers in dealing with language issues during their online classes. Findings indicated the frequent occurrence of LREs during interpersonal interaction in both online classes. The majority of the LREs were initiated by the teachers, and students, too, initiated some LREs. Different patterns were found in the interactional type and linguistic categories of LREs between the different disciplines. Synchronous text-based chat appeared to facilitate students to proactively initiate LREs, mainly to attend to vocabulary and grammar. Findings also revealed that both EMI teachers had more challenges helping students with language in the online context than in the F2F context. Highlights: Content teachers' spontaneous linguistic support in online EMI classes was examined. The nature of LREs in interpersonal interaction including text chat was analysed. LREs in two different classes (history and mathematics) were compared. Linguistic challenges for EMI teachers in remote teaching settings were investigated.